Residential green is associated with reduced annoyance to road traffic and railway noise but increased annoyance to aircraft noise exposure. (October 2020) - Schäffer, Beat; Brink, Mark; Schlatter, Felix; Vienneau, Danielle; Wunderli, Jean Marc
Highlights: Residential green reduces road traffic and railway noise annoyance. The annoyance reduction is equivalent to 6 dB (road) and 3 dB (rail). Residential green is associated with increased aircraft noise annoyance. The annoyance increase is equivalent to 10 dB (air). Quality attributes of residential green depend on the degree of urbanization. Abstract: Background: In recent years, residential green and availability of neighbourhood green spaces came into focus as a potential means to reduce transportation noise annoyance. Literature suggests that various characteristics of residential green may play a role, namely, greenness of the residential areas as quantified by the normalized difference vegetation index (NDVI), visible vegetation from home, and the presence of public green spaces as identified by land use classification data (LU-green), as well as their accessibility and noise pollution (i.e., transportation noise exposure within green areas, how loud/quiet they are). So far, studies mostly focused on road traffic noise in urban areas. Objective: We investigated the effects of residential green on noise annoyance, accounting for different transportation noise sources as well as for the degree of urbanisation. Methods: We complemented the data set of the recent Swiss SiRENE survey on road traffic, railway and aircraft noise annoyance with a wide range of "green" metrics, and investigated their association with annoyance by means of logistic regression analysis (generalized estimating equations). Results: Increasing residential green was found to be associated with reduced road traffic and railway noise annoyance, but increased aircraft noise annoyance. The overall effect corresponded to equivalent level reductions of about 6 dB for road traffic and 3 dB for railway noise, but to an increase of about 10 dB for aircraft noise, when residential green increased from "not much green" (5th percentile of the study sample distribution) to "a lot of green" (95th percentile). Overall, NDVI and LU-green were particularly strongly linked to annoyance. The effects of visible vegetation from home and accessibility and/or quietness of green spaces were, overall, less strong, but depended on the degree of urbanisation. For road traffic noise, visible vegetation and accessibility of green spaces seem to particularly strongly reduce annoyance in cities, while quiet green spaces are more effective in rural areas. Conclusions: Our study emphasizes that residential green should be fostered by city planners, particularly in densely populated areas.